Theory of mind deficits in language delayed deaf subjects?: A reconsideration of evidence from false belief tasks - Begby, Endre (Philosophy and the mind sciences, 2023)
Recent studies claim to show that language delayed deaf subjects typically display longlingering deficits in Theory of Mind (ToM) development, despite suffering no known deficits in other cognitive domains. These claims are supported by experimental evidence indicating that such subjects fare poorly on False Belief (FB) tasks. This paper turns a critical eye on these claims. In particular, I argue that the reported results raise important questions about the status of FB tasks as evidence, and about how such evidence should be weighted against naturalistic observations of subjects engaged in everyday activities requiring complex social coordination. I conclude that these studies give us no decisive reason to believe that language delayed deaf subjects suffer distinctively and symptomatically in the domain of social cognition. To the contrary, the attribution of significant socio-cognitive impairment is potentially stigmatizing and may not help us understand the unique challenges these subjects face or suggest remedial strategies to aid them in overcoming these challenges.